Depressive states in the structure of postcovid syndrome: features and therapy - N N Petrova; A V Kudryashov; O V Matvievskaya; A A Mukhin; V A Lavrova; E M Chumakov; N V Yaltseva; S V Kuzmina; N V Kostina; E V Akimova; K S Sadovnichiy; A V Antsyborov; et al. (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2022)
The article provides a review of the scientific literature devoted to postcoid conditions. The concept of postcovid syndrome, its structure, and epidemiology are disclosed. The article contains the results of 2 meetings of experts (psychiatrists, psychotherapists, neurologists) from different regions of Russia who had experience in providing care to persons with postkovid syndrome. Particular attention is paid to postcovid depression, its clinical characteristics, and the experience of therapy. It was noted that the severity of the post-coV syndrome did not depend on the severity of the infectious disease suffered. The leading variants of depressive syndromes observed in SARS-CoV-2 patients were: astheno-depressive, apato-depressive and anxious-depressive syndromes. Anhedonia, anxiety, cognitive disorders, insomnia, and hypochondria occupied a significant place in the structure of postcovid mental disorders. It is emphasized that persons with postcovid syndrome, as a rule, initially found themselves in the field of vision of internists, therefore, their training in the diagnosis of postcovid mental disorders is relevant. Clinical experience has demonstrated the feasibility of antidepressant therapy for postcovid depression and the high efficacy and safety, including the risk of drug interactions, of using vortioxetine, including prescribing the drug to the elderly and the somatically impaired. The article is illustrated with clinical examples.